Experimental investigation of plasma spraying on curved surface - Lim, Meng Han. (2011)
Plasma spraying is a complex process in which the final coating is governed by various parameters. One of the most important factors is the effect of surface topology on coating profile which is the focus of this study. The simple model of a convex surface would be used as substrate for this study. Relationship between the final coating properties with the particles impact angle on the substrate would be established. The eventual goal is to develop a methodology capable of simulating the coating formation on a complex surface. As coating consists of individual droplet named splat overlapping on each other, experiment was conducted to capture single splat along the concave surface to cover the entire range of splat under different impact angles. The coating material used was Yttria-partially stabilized zirconia (YSZ) powder. The splats morphology would then be observed and analyzed using optical microscope, confocal microscope, and scanning electron microscope (SEM). Images and data points of splats acquired from these microscopes would be further processed using dedicated software to calculate the aspect ratio and spread factor. They are the two most important parameters that describe the splat morphology and their relationship with respect to different impact angle on the convex substrate would be obtained. The in-flight particles behavior of average velocity, heading angle, and temperature in plasma plume prior to impact were measured using SprayWatch imaging CCD camera.